PENGHINDARAN DAN PENGELAKAN BENTUK USAHA TETAP: Analisis Hukum dalam Hukum Pajak Internasional - Zahra, Marshanda Cahyani; Maharani, Audriana Putri; Tuhfaturrahmah, Balqis (International Journal of Multidisciplinary Research and Literature, 2026)
This study explores the phenomenon of Permanent Establishment (PE) avoidance and evasion in Indonesia by examining how multinational companies design their business arrangements to limit tax exposure in the source country. Using an analytical approach that combines regulatory analysis, illustrative cases, and evidence from prior empirical studies, the paper uncovers several recurring practices, including the appointment of ostensibly independent agents, the deliberate separation of operational activities, the maintenance of minimal physical operations, and the increasing reliance on digital business models. In addition, the research reviews the alignment and performance of Indonesia’s domestic tax framework with OECD standards, while emphasizing ongoing difficulties linked to sophisticated corporate configurations, the rapid expansion of digital transactions, and unequal access to information between taxpayers and tax authorities. The results demonstrate that although Indonesia has formally incorporated internationally recognized rules, their effectiveness is constrained at the implementation level. Accordingly, the study highlights the necessity of reinforcing oversight mechanisms, enhancing international tax cooperation, and adopting a significant economic presence concept to more accurately address digitalized and cross-border economic activities. This research advances the academic discussion on PE-related tax avoidance and offers policy-relevant insights for legislators, tax administrators, and future researchers.